Improving Fine Motor Skills in Children Aged 4-5 Years through Paper Tearing Activity - Pingky Nur Azizah; Warananingtyas Palupi; Glenn Webforges D. Ricardos (Universitas Sebelas Maret, 2026)
This study was motivated by the problem of underdeveloped fine motor skills among children aged 4–5 years in one kindergarten in Serengan District, Surakarta City, although these skills are one of the main prerequisites for early childhood academic readiness. This study aimed to improve children’s fine motor skills through paper-tearing stimulation. The study employed both quantitative and qualitative approaches. The research design was classroom action research based on the Kemmis and McTaggart model, consisting of three stages: planning, action, observation, and reflection. The participants were 21 children aged 4–5 years, and data were collected from children and teachers. Data were collected through observation, interviews, tests, and documentation. Qualitative data validity was examined through source and technique triangulation, while quantitative data validity was examined through construct validity based on expert judgment. Qualitative data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing/verification. Quantitative data were analyzed using the mastery learning formula for children. The results showed that paper-tearing activity improved children’s fine motor skills. In the finger strength and flexibility indicator, 19 children (90.5%) achieved mastery. In the hand–eye coordination indicator, mastery reached 100%. In the finger movement accuracy indicator, 20 children (95.2%) achieved mastery. These findings indicate that paper-tearing activity can improve the fine motor skills of children aged 4–5 years.